Etika Profesi Akuntan dan Kepatuhan Terhadap Standar Akuntansi Keuangan pada Perusahaan Manufaktur Farmasi: Studi Kasus PT Indofarma - Angel Pintauli Rosita; Fathira Nurul Jannah; Wanda Amelia Paramitha; Calista Margaretha Tumbelaka; Yanuar Ramadhan (Lembaga Pengembangan Kinerja Dosen, 2026)
This research looks into the moral breaches made by accountants and how well they follow the Financial Accounting Standards at PT Indofarma Tbk, a drug-making firm in Indonesia. The goal of the study is to find out what leads to financial wrongdoing. The research takes a qualitative approach by looking at audit papers and financial statements from the Supreme Audit Institution from 2020 to 2023. The results uncover various dishonest activities, including inflated inventory, fake transactions, and wrongful discounts. These actions led to a national loss of Rp 371.8 billion and broke the ethical standards of the accounting field, harming the reputation of both the accountants and the organization. The analysis of the findings is connected to theories about professional ethics and corporate governance. The theoretical input of this research aims to improve the understanding of how ethical violations influence the use of Financial Accounting Standards and the quality of financial reports in the pharmaceutical manufacturing sector. On a practical level, the study suggests ways to enhance internal checks and provide ethics training to boost the honesty of financial reporting. A limitation of this research is the reliance on secondary data, indicating that more studies with primary data are necessary for clearer findings.